2021
DOI: 10.3390/su132112126
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Materials for Printed Circuit Board Production: An Environmental Perspective

Abstract: This article investigates the potential environmental impacts of four-layer printed circuit board (PCB) production from cradle to grave. The study starts with a lifecycle assessment of conventional PCB production. Then, the alternative materials of polyethylene terephthalate (PET), polylactic acid (PLA)/glass fiber composite and paper are investigated for the substrate. A conventional PCB adopts copper as the conductive material and requires an etching process. The environmental impacts of changing the conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…Demonstration projects have shown that the use of materials such as paper, flax and biobased resin matri ces in prototype PCBs can reduce the environmental impacts of source materials and improve recovery and reuse of metals and electronic components, minimize the use of toxic flame retardants, and provide pathways for safer end of life management [5][6][7] . Ensuring high level www.nature.com/natrevmats 0123456789();: performance and long term reliability for such biobased substrates has proven elusive, in part because of techni cal challenges associated with their tendency to retain moisture 8 .…”
Section: Towards Sustainable Pcbsmentioning
confidence: 99%
“…Demonstration projects have shown that the use of materials such as paper, flax and biobased resin matri ces in prototype PCBs can reduce the environmental impacts of source materials and improve recovery and reuse of metals and electronic components, minimize the use of toxic flame retardants, and provide pathways for safer end of life management [5][6][7] . Ensuring high level www.nature.com/natrevmats 0123456789();: performance and long term reliability for such biobased substrates has proven elusive, in part because of techni cal challenges associated with their tendency to retain moisture 8 .…”
Section: Towards Sustainable Pcbsmentioning
confidence: 99%
“…With the growth in the field of printed electronics, the question of replacing conventional PCBs with novel printed electronics arises. Given that the fabrication of FR4 is energy-intensive, utilizes fossil materials such as epoxy-resin, has limited recyclability, and that etching the circuit design requires substantial chemical and energy input (Nassajfar et al, 2021;Premur et al, 2016), printed electronics seem to trump PCBs in the context of sustainability. Printed electronics offer the possibility of electronics that are resource-efficient to manufacture and have non-fossil, renewable, biodegradable, and biocompatible substrates that are free from toxic flame retardants (Irimia-Vladu, 2014; W. Li et al, 2020;Liu et al, 2014).…”
Section: (B)mentioning
confidence: 99%
“…Additionally, a chemically resistant masque is deposited on the conductive surface according to the circuit design. Finally, the excess Cu is etched away to reveal the conductive circuit design by submerging the FR4 laminated with Cu in a chemical bath (Esfandyari et al, 2015;Nassajfar et al, 2021;Patel, 2018). Conceptually, the manufacturing of PCBs involves the removal of excess Cu through etching or lithography and is therefore classified as a subtractive manufacturing process (Kunnari et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1 Currently, the standard for printed circuit board (PCB) substrate materials are centered around glass fiber, resin, and copper composites, which are rigid and bulky and require relatively intensive manufacturing processes. 2 These exhaustible materials are especially unsuitable for and misallocated to single-use, disposable electronic devices, including but not limited to those in the fields of point-of-care diagnostics, environmental biomonitoring, and wearables. 3 Replacing conventional electronic materials with cellulose paper substrates has numerous advantages.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, paper-based electronic circuits have gained increasing attention as a promising alternative to conventional circuit materials . Currently, the standard for printed circuit board (PCB) substrate materials are centered around glass fiber, resin, and copper composites, which are rigid and bulky and require relatively intensive manufacturing processes . These exhaustible materials are especially unsuitable for and misallocated to single-use, disposable electronic devices, including but not limited to those in the fields of point-of-care diagnostics, environmental biomonitoring, and wearables .…”
Section: Introductionmentioning
confidence: 99%